MENINGKATKAN KEMAMPUAN MEMBACA KATA MELALUI METODE FONETIS BAGI ANAK TUNAGRAHITA SEDANG - Sri Nurzalenawati Elly (Universitas Negeri Padang, 2013)
This study in latarbelakangi from reality that occurs in school mental retardation in children who have not been able to read words with benar.di appeal to his friend who was able to read sentences sederhana.Kemampuan reading nouns associated with the name of the body consists of two syllables expected. There are differences in the ability to read is still at the stage of reading one syllable. This stage in view of still less when compared with two classmates who can read simple sentences. Type of study used action research (classroom action research) is research conducted by teachers, working with researchers (or done by teachers themselves who also acted as a researcher) in the classroom or in the school where he taught. The procedures in this study covers four stages as follows: (1) Planning, (2) implementation, (3) observation, and (4) Reflection. If the problem is not resolved, it will be re-done re-planning, re-act, observe and reflect again until the problem can be solved. Approach to action research was conducted in two cycles. Cycle one shows that through phonetic method can increase the child's ability to read words 2 words correctly. it is evident from the analysis that the implementation of the practice sheet reading phonetic method. After being given a second treatment cycle with the phonetic method proven to increase children kemempuan read the six words read correctly. Advised the teachers to apply learning methods to improve reading phonetic words.